Once were Warriors – a Model that Matters and a Mirror of Concerns - Ramstad, Jorun Bræck (Nordlit, 2012)
In this article, I will focus on connections between media, culture and society in order to understand two prototypical Maori responses to the film. The two kinds of responses are captured in the following phrases: “The film should never have been made” and “That’s not fiction, that’s reality”. One of my objectives is to show how these particular Maori responses to this fiction-film are entangled with deep concerns about ethnic policies and marginalization in general. In other words, the film is explored as a statement about Maori – Pakeha inter-ethnic relations and ‘biculturalism’, which is the official term for the political vision of the post-colonial nation. Subsequently, my analysis suggests insights from a deeper concern about the contexts that contribute to these particular Maori formulations of media-reality configurations, in addition to lessons of a more general character.